Systematic Review on the Impact of Venezuelan Migration in Colombia: Analysis of Socioeconomic Consequences (2016-2023) - Galvis Vega, Luis Alveiro (Sociedad y Economía, 2025)
This article provides a comprehensive compilation of information published between 2018 and 2023 regarding the socio-economic impacts generated in Colombia due to the extensive Venezuelan migration, which peaked between 2016 and 2019. Employing the PRISMA method and considering the WOS and SCOPUS databases, 39 relevant articles were identified and analyzed. From these, the systematic review revealed significant data regarding key consequences, with a primary focus on health, education, security, and the Colombian economy. This stems from the fact that the majority of examined articles address these social and cultural aspects, offering a comprehensive insight into the challenges and opportunities arising in the context of Venezuelan migration in Colombia.